Athabasca University: Conversion from Traditional Distance Education to Online Courses, Programs and Services - Alan Davis (Athabasca University Press, 2001)
In its 30 years of operation, Athabasca University has witnessed the full impact of the growth of online distance education. Its conversion from mixed media course production and telephone/mail tutoring to a variety of electronic information and communication technologies has been heterogeneous across disciplines and programs. Undergraduate programs in business, computing, and some social science programs have largely led the conversion, and all graduate programs have, since their inception, employed various features of online delivery. The parallel conversion of student services has been equally important to the effectiveness of these processes. The implications of this approach for the quality of offerings, support systems, costing, and the primary mandate of the University (which is to remove barriers, not create them) are discussed.